Analisis Usability pada Perancangan Sistem Informasi Manajemen Aset Gudang Berbasis Web Menggunakan Metode Prototyping dan System Usability Scale (SUS) - Sri Dianing Asri; rubiyatno (JSAI (Journal Scientific and Applied Informatics), 2026)
Operational asset management plays a strategic role in ensuring the smooth and continuous operation of warehouse activities within a company. PT. Indomarco Prismatama faces challenges in managing assets, particularly in the processes of asset borrowing, return, and maintenance, which are still conducted manually. This results in potential delays in data recording, reduced data accuracy, and limited information transparency. This study aims to design a web-based information system for managing asset borrowing, return, and maintenance to improve efficiency and accuracy. The system was developed using the Software Development Life Cycle (SDLC) methodology with a prototyping approach, which allows for user involvement through iterative stages. The system was built using the CodeIgniter 4 framework and a MySQL database. System testing was performed using the System Usability Scale (SUS) method, involving 20 respondents, including Asset Admins, VUM Admins, and Managers. The evaluation results show an average SUS score of 81.9, indicating a high level of usability (Excellent). However, these results are limited to the current group of respondents and may not represent a broader user base. Overall, the developed system supports more effective, efficient, and transparent operational asset management, although further testing is needed to confirm its scalability and usability across a wider audience.